Genetic Diversity of Rhizophora mucronata in Rote Island, Indonesia Based on RAPD Molecular Marker - Ihwan, Ihwan; Uslan, Uslan (Universitas Brawijaya, 2025)
The coastal region of Rote Island is predominantly inhabited by Rhizophora mucronata. However, there is a lack of information about the genetic diversity of this mangrove species. This study aimed to determine the genetic diversity of Rhizophora mucronata on Rote Island, Indonesia, using RAPD molecular markers. We collected 21 R. mucronata samples from seven coastal sites on Rote Island, and subsequent data analysis occurred at the Genetic and Molecular Laboratory of UIN Maulana Malik Ibrahim Malang. Clustering analysis was carried out using PAST software (version 3.15). The findings indicated that 10 out of the 15 tested primers (OPA 2, OPA 3, OPA 4, OPA 5, OPA 6, OPA 7, OPA 8, OPA 10, OPA 19A, and OPA 20) yielded successful outcomes, resulting in the production of polymorphic bands. This finding indicates an elevated degree of genetic diversity among the samples under consideration. The genetic diversity values (He) for the R. mucronata population on Rote Island were found to be 0.244 (moderate category), with the highest genetic diversity value (He) of 0.465 recorded at Oelaba, while the population demonstrating the lowest genetic diversity was 0.100 at Pantai Baru. Notably, the population grouping of R. mucronata on Rote Island did not correlate with geographical positioning.